FIDES QUAERENS PULCHRUM: PRACTICAL THEOLOGICAL PERSPECTIVES ON THE DESIRE FOR BEAUTY - Cilliers, Johan (Scriptura, 2011)
In this article, the notion of 'desire' is critically interpreted in terms of the classic theological notion of 'quaerens' (as for instance in: fides quaerens intellectum; faith in search of understanding). 'Quaerens' indicates the quest for (or paradox of) something that is not yet attained, although already experienced, here understood as a quest for beauty - fides quaerens pulchrum. The concept of beauty is multi-layered, but traditionally it is viewed in a romanticized sense, as something (or an experience) that is fine, excellent, noble and honourable. In this article this romanticized view is critiqued within an aesthetical understanding of practical theology, in which beauty is understood as the quest for a radically different (and paradoxical) form of proportion within the experience of pain, horror and destruction. In this sense beauty is not contradicted by the notion of ugliness, but rather indicates the quest for the healing of proportions and the connection between the visual and transcendent meaning. The article takes a brief look at the development of some paradigmatic shifts in practical theological methodology, before discussing possible aesthetical practical theological meanings of beauty. doi: 10.7833/108-1-1